O campo vai à cidade: uma abordagem bibliométrica da questão espraiamento e adensamento nos estudos urbanos - Lucas Veloso de Menezes (2014)
This thesis focuses on the "Urban Studies", using the framework of Scientific Field as proposed by Pierre Bourdieu. In this authors perspective, in order to understand a field of scientific social studies and knowledge, means grasping its place and importance in the academic sphere and in wider social life, as well as the internal boundaries of its political, social and intellectual exercise, via interactions involving scientific knowledge. Also by understanding political and social validation processes and the conditions of exercise and relations of actors and practitioners, involving both competition and collaboration. Working with the concept of field also involves knowing the topography of its themes and the delimitation of the visions, knowledge and methodological instruments of social reality creation and transformation. The Urban Studies are relatively unexplored field in Bourdieus perspective. In essence, the concept is about a multidisciplinary field incorporating different areas, which, have not until recently, been integrated (especially in Brazil), as result of the idea predominance of disciplinary specialization and reductionist views prevalent in the twentieth century. Thus, the possibility of greater coordination and multidisciplinary integration of this field is relatively recent and currently incomplete. In this century, the processes of urbanization expand and diversify requiring trans, multi and interdisciplinary, holistic and more complex visions of the urban phenomena, as espoused in this work, resulting in seeking information that can help pave the integration and complexity of its evolution in contemporary times. One of the methods used to conduct studies of scientific fields is bibliometrics, via meta-analysis parameters for collection and articulation of outcomes, processes of quantification / qualification of content to identify the scope and scale of a field. Among its applications is the ¯mapping of the area" that aims disentangling how a certain field works, which themes, methodologies and how discoveries are disclosed. In Urban Studies, this methodology is practically nonexistent. Research developed in specialized journals revealed one such study conducted for the field of urban studies, developed by Zao Liu (2005). In this aspect, in Urban Studies, the present Thesis is the second study doing this kind of approach and first undertaken in Brazil. One of the recurring Urban studies fields scholarly debates was used as the starting point of research: the dichotomy density/sprawl. Based on this debates keywords searches on articles were carried out on these topics, in association with seven chosen related topics. Bibliometrics keyword search carried out in 87 journals, allowed selection of 1,537 articles and these items analyzed in quantitative basis, as far as the incidence of subjects, languages and periodicals, as well as the thematic inter relationship. In addition, though a qualitative approach, based in content analysis, categorical techniques were used to studying the types of articles contents and to map research distribution (by countries, cities and institutions) and degree of institutional cooperation. For the content analysis, two approaches used were general survey (all items) and articles in Portuguese. In the aim of better understanding the field, currents of thoughts analyzed, as well as two types of Brazilian institutions: postgraduate courses and a national research directory. Quantitative and qualitative (content) analyses carried out, for the collected data, as well as the dissertations defended in the field next to graduate from the School of Architecture of UFMG.